Establishing the reliability of instrumented trunk impairment assessment methods to enable evidence-based classification in Para swimming. (13th August 2021) - Smith, Rachel; Connick, Mark; Beckman, Emma; Hogarth, Luke; Nicholson, Vaughan
ABSTRACT: This study examined the reliability of instrumented trunk assessment methods across two experiments to develop and improve evidence-based classification in Para swimming. Trunk coordination, range of motion (ROM), and strength were assessed in 38 non-disabled participants. Each test battery was completed on two occasions to determine inter-session reliability. Intra-session reliability was also determined in Experiment Two. Absolute agreement of two-way mixed intraclass correlation coefficients (ICC 3, 1) was calculated to assess reliability. Standard errors of measurement (SEMs) were also reported to facilitate comparisons between different outcomes. Trunk coordination measures had low-to-moderate reliability (inter-session ICCs = 0.00–0.60; intra-session ICCs = 0.14–0.65) and variable SEMs (5–60%). Trunk ROM demonstrated moderate-to-excellent reliability (inter-session ICCs = 0.61–0.93; intra-session ICCs = 0.87–0.95) and good SEMs (<10%). Trunk strength measures demonstrated good-to-excellent reliability (ICCs = 0.87–0.98) and good SEMs (<10%). The strength values obtained for the load cell and hand-held dynamometer (HHD) were significantly different from each other with the HHD underestimating strength. Modifications provided in Experiment Two improved the reliability of strength and ROM assessments but did not improve coordination measures. Further research involving para swimmers is required to establish the validity of the methods.